Familial adenomatosis coli: surgical treatment with cellular transplantation - Yu. A. Shelygin; A. M. Kuzminov; D. V. Vyshegorodtsev; L. L. Kapuller; G. T. Sukhikh (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To develop reconstructed mucosa of the rectum for improvement results of surgical treatment of familial adenomatosis polyposis coli (FAP).Material and methods. Overall 27 patients with FAP underwent surgical treatment including colectomy, demucosation of rectum and allogenic transplantation of fetal intestinal epithelium cells and mesenchyma of various origin to develop reconstructed mucosa. In 5 patients the ileorectal anastomosis, in 22 – small-intestinal reservoirs were created.Results. During period from 4 to 12 wks development of rectal mucosa was observed in all patients. At follow-up from 1 year to 5 years no proliferation of polyps was revealed in 26 (96,3%) patients.Conclusions. Cell transplantation can successfully be applied for development of reconstructed rectal mucosa. Keeping part of rectum after colectomy and formation of smallintestinal reservoir allows to keep natural intestinal passage with good functional results.